Pakistani Leaders’ Response to the Challenge of Power Politics by Bengali Separatism - Rizwan Ullah Kokab and Mahboob Hussain (Journal of Political Studies, 2014)
One of the important facet of Bengali separatist movement since its origin in 1948 was Bengalis’ struggle to share political power. The power politics of Bengalis was one of the challenges for the leadership of Pakistan in terms of separatist movement that succeeded in 1971. This paper examines the political strategies and tactics of Pakistani leaders, which they adopted in response to those of Bengali politicians. The power sharing of Bengalis, popularity of powerful Pakistani elite and their focus on the political power and not the security of Pakistan in face of Bengali separatism have been analysed in this research paper. The documents and secondary books are major sources of research.